2021
DOI: 10.3389/fpsyt.2021.757685
|View full text |Cite
|
Sign up to set email alerts
|

Do Anxiety and Depression Predict Persistent Physical Symptoms After a Severe COVID-19 Episode? A Prospective Study

Abstract: Background: Persistent physical symptoms are common after a coronavirus disease 2019 (COVID-19) episode, but their pathophysiological mechanisms remain poorly understood. In this study, we aimed to explore the association between anxiety and depression at 1-month after acute infection and the presence of fatigue, dyspnea, and pain complaints at 3-month follow-up.Methods: We conducted a prospective study in patients previously hospitalized for COVID-19 followed up for 3 months. The Hospital Anxiety and Depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
3
25
0
2
Order By: Relevance
“…The persistent symptoms of long COVID-19 appear to affect cognitive and physical function, health-related quality of life, and participation in society [ 181 ]. For example, Bottemanne et al found that depression after an acute COVID-19 episode might be linked to an increased risk of some persistent physical symptoms, including pain and dyspnea [ 182 ]. Hence, early interventions are crucial to combat the rising psychiatric manifestation of COVID-19 and to improve the functioning and quality of life of those affected, as well as to reduce the chances of developing neurocognitive impairments in addition to the already-debilitating psychiatric manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The persistent symptoms of long COVID-19 appear to affect cognitive and physical function, health-related quality of life, and participation in society [ 181 ]. For example, Bottemanne et al found that depression after an acute COVID-19 episode might be linked to an increased risk of some persistent physical symptoms, including pain and dyspnea [ 182 ]. Hence, early interventions are crucial to combat the rising psychiatric manifestation of COVID-19 and to improve the functioning and quality of life of those affected, as well as to reduce the chances of developing neurocognitive impairments in addition to the already-debilitating psychiatric manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Protracted physical symptoms after COVID-19, including CV and respiratory symptoms, are closely related to a higher probability of developing psychiatric diseases [100][101][102]. Furthermore, post-COVID-19 syndrome might be experienced more strongly by depressed patients, or these dimensions might involve shared factors such as a high level of neuroticism (i.e., tendency to experience negative emotions such as anger, fear or sadness with limited tolerance for aversive stimuli) [103,104]. On the other hand, a rise in the incidence of Takotsubo syndrome seems to be an effect of the COVID-19 pandemic, with the incidence of Takotsubo syndrome rising 4.5-fold during the pandemic even in people without severe acute respiratory syndrome [105].…”
Section: Organ Crosstalk and Management Of Post-covid Conditionsmentioning
confidence: 99%
“…Mild to severe symptoms must be adequately evaluated according to the underlying diagnosis (Figure 4). level of neuroticism (i.e., tendency to experience negative emotions such as anger, fear or sadness with limited tolerance for aversive stimuli) [103,104]. On the other hand, a rise in the incidence of Takotsubo syndrome seems to be an effect of the COVID-19 pandemic, with the incidence of Takotsubo syndrome rising 4.5-fold during the pandemic even in people without severe acute respiratory syndrome [105].…”
Section: Organ Crosstalk and Management Of Post-covid Conditionsmentioning
confidence: 99%
“…187 In one prospective study, the presence of depression at one month after covid-19 infection predicted persistent pain at three months. 188 Because chronic pain, fatigue, sleep disorders, and cognitive difficulties are concurrent in postinfectious syndromes, it can be difficult to infer cause and effect, and these relationships are probably interdependent. One consistent finding across studies is a clear association between chronic pain after infection and poorer quality of life.…”
Section: Psychological Implications Of Infection and Chronic Painmentioning
confidence: 99%